2016
DOI: 10.1136/bmjopen-2016-013414
|View full text |Cite
|
Sign up to set email alerts
|

‘It promoted a positive culture around falls prevention’: staff response to a patient education programme—a qualitative evaluation

Abstract: ObjectivesThe purpose of this study was to understand how staff responded to individualised patient falls prevention education delivered as part of a cluster randomised trial, including how they perceived the education contributed to falls prevention on their wards.DesignA qualitative explanatory study.Methods5 focus groups were conducted at participatory hospital sites. The purposive sample of clinical staff (including nurses, physiotherapists and quality improvement staff) worked on aged care rehabilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Of the included articles, five were systematic reviews (Table 1) [14,37,[47][48][49], three were targeted literature reviews [6,50,51], 10 were randomised controlled trials (RCTs) ( Table 2) [30-32, 34, 38, 52, 53, 55, 57], three were qualitative studies [58][59][60], and three were unpublished theses [61][62][63]. The remaining studies were quasiexperimental trials (n = 18).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included articles, five were systematic reviews (Table 1) [14,37,[47][48][49], three were targeted literature reviews [6,50,51], 10 were randomised controlled trials (RCTs) ( Table 2) [30-32, 34, 38, 52, 53, 55, 57], three were qualitative studies [58][59][60], and three were unpublished theses [61][62][63]. The remaining studies were quasiexperimental trials (n = 18).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Haines et al [64] examined economic evaluations of falls prevention programs following an RCT [30]. Three qualitative studies reported staff [58], educator [59] and participant perspectives [60] following an intervention carried out in an earlier study [38]. For the purposes of this scoping review, investigations such as these were analysed together.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, one trial [ 19 ] had three qualitative studies published in the same journal: a qualitative interview study labelled as ‘a process evaluation’ [ 31 ], a qualitative questionnaire study reported as ‘informing the process evaluation’ [ 30 ], and a qualitative interview study labelled as a ‘qualitative evaluation’ [ 29 ]. However, the articles indicated that the studies were interlinked and formed a ‘sequential mixed-methods study’ [ 31 ].…”
Section: Resultsmentioning
confidence: 99%